Training on Making Healthy Dumplings from the Flesh of Manalagi Mango Typical of Local Fruit from SMA Muhammadiyah Kedawung School - Nurudin, Arif; Gusman, Tania Avianda; Hasanah, Uswatun; Nurdiyanti, Dewi (Society : Jurnal Pengabdian Masyarakat, 2025)
This training aims to improve students' skills through the utilization of manalagi mango pulp as a basic ingredient for making healthy dumplings to become a superior product for students of SMA Muhammadiyah Kedawung. The activity was carried out at SMA Muhammadiyah Kedawung with a participatory approach. The methods used included observation, implementation in the form of socialization and training, and evaluation in the form of pretests and posttests. Students were taught how to process mango manalagi into healthy dumpling filling that is nutritious and adds economic value. The results of the activity showed an increase in students' skills in the dumpling production process as well as knowledge about dumpling nutrition. Student response was very positive, with 85% of participants showing interest in improving their understanding of processing fruit pulp into nutritious and healthy dumplings.